Optimized graphene electrodes for contacting graphene nanoribbons. (30th October 2021) - Braun, Oliver; Overbeck, Jan; El Abbassi, Maria; Käser, Silvan; Furrer, Roman; Olziersky, Antonis; Flasby, Alexander; Borin Barin, Gabriela; Sun, Qiang; Darawish, Rimah; Müllen, Klaus; Ruffieux, Pascal; et al.
Abstract: Atomically precise graphene nanoribbons (GNRs) are a promising emerging class of designer quantum materials with electronic properties that are tunable by chemical design. However, many challenges remain in the device integration of these materials, especially regarding contacting strategies. We report on the device integration of uniaxially aligned and non-aligned 9-atom wide armchair graphene nanoribbons (9-AGNRs) in a field-effect transistor geometry using electron beam lithography-defined graphene electrodes. This approach yields controlled electrode geometries and enables higher fabrication throughput compared to previous approaches using an electrical breakdown technique. Thermal annealing is found to be a crucial step for successful device operation resulting in electronic transport characteristics showing a strong gate dependence. Raman spectroscopy confirms the integrity of the graphene electrodes after patterning and of the GNRs after device integration. Our results demonstrate the importance of the GNR-graphene electrode interface and pave the way for GNR device integration with structurally well-defined electrodes. Graphical abstract: Image 1